The Synergies Between Educational Philosophy Streams and Ki Hajar Dewantara's Ideologies in the Mardeka Belajar Curriculum - Hunaepi, Hunaepi; Suastra, I Wayan; Tanjung, Henra Saputra; laia, Bestari; Raharjo, Raharjo (Reflection Journal, 2023)
The synergy between educational philosophical streams and the thoughts of Ki Hajar Dewantara is crucial in developing the concept of the "Merdeka Belajar" curriculum in Indonesia. This literature study aims to explore the fusion between relevant educational philosophical streams with the vision and principles advocated by Ki Hajar Dewantara in the context of developing the "Merdeka Belajar" Curriculum. The method used is descriptive analysis through a literature review drawn from relevant and credible academic texts to trace Ki Hajar Dewantara's thoughts and comprehend the fundamental concepts of educational philosophy underlying it. The findings from this analysis indicate that the synergy between educational philosophy and Ki Hajar Dewantara's thoughts within the "Merdeka Belajar" Curriculum holds immense potential in transforming Indonesia's educational system. By integrating philosophical principles and embracing Ki Hajar Dewantara's ideas, educators can create a curriculum that nurtures individuals with broad perspectives equipped with the skills and values necessary for thriving in the 21st century. The integration of these values in the "Merdeka Belajar" Curriculum can foster an inclusive, progressive learning environment oriented towards character development and individual potential. The application of synergy between educational philosophical streams and Ki Hajar Dewantara's thoughts in the "Merdeka Belajar" Curriculum can reinforce the essence of holistic and continuous education. Recommendations include the necessity of developing concrete strategies to integrate educational philosophical values with Ki Hajar Dewantara's principles in every aspect of the curriculum, providing training for educators to implement this approach, and conducting further research to evaluate the effectiveness of the "Merdeka Belajar" Curriculum implementation inspired by this synergy